Role of endoscopic retrograde cholangiopancreatography after orthotopic liver transplantation. Issue 4 (April 1991) - O'Connor, H J; Vickers, C R; Buckels, J A; McMaster, P; Neuberger, J M; West, R J; Elias, E
Abstract : Twelve of 178 (7%) liver transplant patients underwent endoscopic retrograde cholangiopancreatography (ERCP) after transplantation. The indications for ERCP were persistent or late onset cholestasis, recurrent cholangitis, and suspected biliary leaks or strictures. The time between transplantation and ERCP ranged from 44 to 330 days (median 153 days). Biliary complications diagnosed by ERCP included biliary sludge in the form of casts, calculi, or debris (n = 7); bile leaks (n = 2); a biliary stricture (n = 1), and complete biliary obstruction (n = 1). One patient had a normal cholangiogram after transplantation. Biliary sludge was detected by ultrasound before ERCP in only one of six patients. Eight patients underwent endoscopic papillotomy, followed by clearance of biliary sludge in four and dilatation of a biliary stricture in one. Two patients bled after papillotomy but neither required surgical intervention. At a median follow up of 1.2 years (range 0.5-2.8 years), nine patients are well and three have died. ERCP provides both accurate diagnosis of biliary complications after liver transplantation and treatment that obviates the need for additional surgery in selected patients.